Procedural success and intra-hospital outcome related to left atrial appendage morphology in patients that receive an interventional left atrial appendage closure - Fastner, Christian; Behnes, Michael; Sartorius, Benjamin; Wenke, Annika; El-Battrawy, Ibrahim; Ansari, Uzair; Gill, Ishar-Singh; Borggrefe, Martin; Akın, Ibrahim (Clinical cardiology, 2017)
Background The interventional left atrial appendage (LAA) closure represents an emerging alternative to oral anticoagulation for stroke prevention in certain atrial fibrillation patients. Preliminary results have suggested high procedural success rates and fewer peri-interventional complications; however, there persists an insufficient understanding of the role of many underlying confounding variables (e.g., anatomical characteristics). Hypothesis It was investigated whether varying LAA morphologies influence procedural success as well as in-hospital outcome. Methods Sixty-seven patients ineligible for long-term oral anticoagulation were included in this single-center, prospective, observational registry spanning from the years 2014 to 2016. Interventions were performed with the Watchman occluder (Boston Scientific, Natick, MA) or the Amplatzer Amulet (St. Jude Medical, St. Paul, MN), at the operator's discretion. Results derived from the data describing procedural success, fluoroscopy, and peri-interventional safety events were classified according to the presenting LAA morphology (cauliflower, cactus, windsock, and chicken wing). Results Rates of successful implantation were high across all groups (≥98%; P = 0.326). Surrogate parameters underlining procedural complexity like median total duration (P = 0.415), median fluoroscopy time (P = 0.459), median dose area product (P = 0.698), and the median amount of contrast agent (P = 0.076) demonstrated similar results across all groups. Likewise, the periprocedural complication rate was not significantly different and was mainly restricted to minor bleeding events. Conclusions Irrespective of the varying morphological presentation of the LAA, the procedural success rates, interventional characteristics, and safety events did not significantly differ among patients receiving an interventional LAA closure.